ETIKA PROFESIONAL DITEMPAT KERJA - Hendriani, Susi; Garnasih, Raden Lestari; Fitri, Kurniawaty; Roesdi, Rosnelly; Pramadewi, Arwinence; Suryatiningsih, Dewita; Efni, Yulia (Komunitas Manajemen Kompetitif, 2025)
Higher education institutions continually strive to improve the quality of graduates to ensure their competitiveness in the workforce. Therefore, they strive to equip students with a variety of skills, both hard and soft. Hard and soft skills development is embedded in courses within a competency-based curriculum, incorporating case-based and project-based learning.In addition to the knowledge of hard and soft skills acquired in college, students are also given the opportunity to gain practical experience through internships. Undergraduate Management students undertake internships in their seventh semester as part of the required coursework to earn a Bachelor of Economics degree. In the 2025-2026 academic year, 260 students from the class of 2022 will undertake internships. They will be placed in departments aligned with their respective concentrations, including human resources, marketing, finance, or operations.Students are now actively seeking internships, both in government and private institutions, through various programs offered, through MBKM internships, or through independent internships. Students entering the workforce, particularly through internship programs, often face challenges in understanding and applying professional ethics in the workplace, often in a work environment that is unfamiliar to them. This lack of understanding can negatively impact performance, interpersonal relationships, and the institution's image.